Implementasi Algoritma K-Means Clustering dalam Penentuan Klasifikasi Tingkat Pembangunan Perekonomian di Provinsi Bali - Sandi, Wijaya Kusuma; Dwidasmara, Ida Bagus Gede (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2023)
Inequality in economic development is one of the problems faced by regencies/cities in Bali Province. Even though Bali is one of the provinces with a fairly large economic contribution in Indonesia, most of its economic resources are still centered in one area. This study aims to form a cluster of districts/cities in Bali Province based on the performance of regional human and economic development using the K-Means Clustering method in order to support an even distribution of economic development in Bali by making regional-based policies that are in adaptability to the level of the economy. The study result showed that three clusters were formed with the first cluster consisting of Klungkung, Karangasem, Bangli, and Jembrana regencies, the second cluster consisting of Badung Regency and Denpasar City, and the third cluster consisting of Gianyar, Buleleng, and Tabanan regencies. Keywords:  Pembangunan Ekonomi, K-Means Clustering, Bali